Factors Associated in the Implementation and Adoption of Electronic Health Records (EHR) in Private Healthcare - Syahirah Mohamad Mobin, Noor; Farik Mat Yatin, Saiful; Razilan Abdul Kadir, Mohd; Noraini Mohd Tobi, Siti; Atiqaf Mahathir, Nur; Norolazmi, Nurzeelawati; Imana Harun, Zakira (International Journal of Engineering and Technology, 2018)
The health industry is undergoing a fast transition from its conventional method of care-giving. E-health or Health Informatics is an ICT-integrated method adopted by the hospitals for providing healthcare services to the patients anytime, anywhere without any restriction of location or facility. Many countries now follow suit to improve efficiency and accuracy in their healthcare systems. Nowadays, many countries including Malaysia still face challenges in the implementation of the healthcare electronic system. Substantial evidence suggests that paper medical records do not provide reliable and updated information on patients. Health physicians provide medical services based on patient history. In cases where this information is inaccurate and/or inaccessible, chances of medical errors due to improper prescriptions remain high.Â Â